Conservation value in indigenous community forests: A case study in the Peruvian Amazon, San Jacinto and Puerto Arturo - Alarcón Aguirre, Gabriel (2018)
The study analyzes the conservation value of forests assigned to indigenous populations of the Peruvian Amazon: San Jacinto and Puerto Arturo in Madre de Dios, communities with different realities in terms of conservation and forest management. Two scenarios prevail here: The San Jacinto indigenous community with 7 033,98 ha of forest, is characterized by disorder and the development of activities that put the community at risk (gold mining), while Puerto Arturo with 3 731 ha is a community committed to the management and conservation of its resources. By means of the Contingent Valuation Method (CVM) through the dichotomous logit model we try to define the willingness of the individuals to accept compensation (WAC) on proposed prices of a hypothetical scenario. The results show that the average annual WAC to implement the environmental program was S/ 20,46 (USD 6,30) and S/ 14,84 (USD 4,57) ha/year respectively. The difference of the WAC is deductible and is product of the levels of impact suffered by both communities due to deforestation, mainly gold mining. Also, these values have an indirect relationship between the income of the indigenous population and potential dangers that affect community forests, while education shows a very significant direct relationship in the WAC. Finally, the forest is important by itself for the indigenous population, and they express a positive disposition for its improvement.